2018
DOI: 10.1051/matecconf/201816503012
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behavior of 316L austenitic stainless steel in air and LWR environment with and without mean stress

Abstract: The fatigue life design curves in nuclear codes are generally derived from uniaxial straincontrolled fatigue test results. Evidently, the test conditions are very different from the actual components loading context, which involves much more complex thermo-mechanical loading including mean stress, static load holding time and variation in water chemistry, etc. In this work, the mean stress and environmental effects on fatigue life of 316L austenitic stainless steel in air and light water reactor (LWR) environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In Figure 4, the ASME design fatigue curve and the fatigue life in air at RT are also presented [4,8]. As is seen, in the same loading condition, the fatigue life of the Z3CN20.09M ASS in water at 300 • C was shorter than that in air at RT [2,3,6,9,[13][14][15]. It indicates that the involvement of corrosive medium or the interactions of corrosive medium with applied load might be responsible for the decrease in the fatigue life of the Z3CN20.09M ASS [16,17].…”
Section: Fatigue Lifementioning
confidence: 98%
See 1 more Smart Citation
“…In Figure 4, the ASME design fatigue curve and the fatigue life in air at RT are also presented [4,8]. As is seen, in the same loading condition, the fatigue life of the Z3CN20.09M ASS in water at 300 • C was shorter than that in air at RT [2,3,6,9,[13][14][15]. It indicates that the involvement of corrosive medium or the interactions of corrosive medium with applied load might be responsible for the decrease in the fatigue life of the Z3CN20.09M ASS [16,17].…”
Section: Fatigue Lifementioning
confidence: 98%
“…Furthermore, the difference in the fatigue life at these three strain rates became more pronounced at higher strain amplitude. It might be caused by the higher corrosion rate of the tested material at higher strain amplitude in the autoclave environments [6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Fatigue Lifementioning
confidence: 99%
“…By combining the setup with heating and cooling apparatus, he manages to characterise at a large range of temperatures. Chen and Spätig use a hollow sample as a containment volume for high temperature hydrogenated water [36]. Kogut and Pan'ko characterise the HE susceptibility of a weld metal by cracking a notched cylindrical specimen, welding the two halves back together over a part of the wall thickness and subjecting it to another test [37].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that SCC and fatigue, i.e., cyclic loading, both are present at a time on many structures of metallic materials [25,26], and the SCC environment (load, environmental conditions, and material susceptibility) has many influences on the fatigue crack growth rate, and vice versa. As an example, strain-induced corrosion cracking (SICC) is used for the situation where cracking takes place under increasing load which may not be increasing necessarily monotonically, but also some cyclic variations are present at start-up and shut down situations of the plants [27]; also during smooth operation, both the loadings, i.e., fatigue (cyclic) and stress corrosion, are present.…”
Section: Introductionmentioning
confidence: 99%